Localization Property for Regular Solutions of the Cauchy Problem for a Fractal Equation of the Integral Form - Litovchenko, Vladyslav (Springer, 2021)
We consider a fractal equation of the integral form with Bessel fractional integrodifferential operator and a positive parameter. In a part of the initial hyperplane, where the limit value has good properties, we establish the property of local strengthening of the convergence of regular solutions with generalized limit values.